2019
DOI: 10.4018/ijgbl.2019070101
|View full text |Cite
|
Sign up to set email alerts
|

Training Law Enforcement Officers to Identify Reliable Deception Cues With a Serious Digital Game

Abstract: Extant research indicates that professional law enforcement officers (LEOs) are generally no better than untrained novices at detecting deception. Moreover, traditional training methods are often less effective than no training at all at improving successful detection. Compared to the traditional training, interactive digital games can provide an immersive learning environment for deeper internalization of new information through simulated practices. VERITAS—an interactive digital game—was designed and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
4
0
2
Order By: Relevance
“…However, the effects of reactance were more pronounced and significant for the law enforcement officer sample. The game-based training was more effective on police off icers when the game used autonomysupportive language within the instruction compared to more controlling language (Miller et al, 2018). One explanation for the difference between the students' responses and the law enforcement officers' responses may be because the latter group is not used to taking orders from university researchers.…”
Section: Reactance To Trainingmentioning
confidence: 99%
“…However, the effects of reactance were more pronounced and significant for the law enforcement officer sample. The game-based training was more effective on police off icers when the game used autonomysupportive language within the instruction compared to more controlling language (Miller et al, 2018). One explanation for the difference between the students' responses and the law enforcement officers' responses may be because the latter group is not used to taking orders from university researchers.…”
Section: Reactance To Trainingmentioning
confidence: 99%
“…Selain itu juga terdapat beberapa permainan yang dapat membantu siswa dalam memahami pembelajaran. Pembelajaran menggunakan media game edukasi ini bertujuan untuk memudahkan proses pembelajaran, menumbuhkan kekreatifan dan inovasi pendidik dalam mendesain pembelajaran yang komunikatif dan interaktif, serta sebagai solusi menghadapi permasalahan di tengah kesibukan pendidikan (An & Cao, 2017;Costa et al, 2017;Gholizadeh et al, 2018;Mclaren et al, 2017;Miller et al, 2019;Moffat et al, 2017;Wilson et al, 2017;Yong et al, Pengembangan media ini menggunakan langkah 4-D, yaitu (1) tahap pendefenisian (define), dengan melakukan analisis kurikulum dan analisis siswa, (2) tahap perancangan (design), dengan menentukan SK, KD, indikator, tujuan, dan materi pokok pembelajaran, mendesain dan merancang media terkait materi yang terdapat pada tema 1 subtema 2, (3) tahap pengembangan (develop), yaitu dengan melakukan uji validitas media kepada ahli (validator), uji praktikalitas media berupa angket kepada siswa kelas V SDN 02 Taluak, dan uji efektifitas media melalui kegiatan evaluasi yang diberikan kepada siswa untuk melihat apakah media yang dikembangkan mampu meningkatkan aktivitas dan hasil belajar siswa, (4) tahap penyebaran (disseminate), dilakukan pembatasan (karena keterbatasan waktu, tenaga dan biaya, sehingga penyebaran hanya dilakukan pada skala terbatas yaitu pada satu sekolah lain) penyebaran di kelas V SDN 03 Tigo Jangko.…”
Section: Kajian Teoretisunclassified
“…Pada usia SD, siswa cenderung lebih tertarik dengan media yang di dalamnya terdapat warna-warna cerah, animasi, serta permainan sehingga akan lebih mudah diingat (Grey, Grey, Gordon, & Purdy, 2017;Jančič & Hus, 2018;Miller et al, 2019). Permasalahan yang ditemui terkait media pembelajaran yang digunakan guru masih kurang inovatif dan kurang tepat guna dalam proses pembelajaran di era revolusi industri 4.0.…”
unclassified
“…Related to serious games, gamification is a process that uses elements of play to modify and enhance pre-existing educational and training practices. Games are constructed to teach a range of topics, including ethics (Brown, 2006), physics instruction (Jackson, 2011), mitigation of cognitive biases (Dunbar et al, 2013), computer coding (Mandaro, 2014), deception detection skills (Miller et al, 2019), and coping with anxiety (Heumos and Kickmeier-Rust, 2020). A meta-analysis that synthesised research findings on game-based learning effects found overall significant, but relatively small, positive effects on cognitive, motivational, and behavioural learning outcomes (Sailer and Homner, 2020).…”
Section: Introductionmentioning
confidence: 99%